ETHNOMUSICOLOGICAL DIMENSION AND MUSICAL ANALYSIS OF THE PRACTICES OF RECITING THE SELA IN THE HARPUT REGION: THE CASE OF MEVLÜT GENÇ - Akca, Ümit; İlhan, Serap Yağmur (Tolga Karaca, 2025)
This study aims to conduct a musical analysis of a specific example of the Sela (call to prayer) performed in the Harput region and to examine the general ethnomusicological dimensions of Harput Selas. Adopting a descriptive approach, this study is designed as a qualitative case study. In this context, in-depth interviews were conducted with a source person who is famous for the Harput region's waterfalls and an expert who is familiar with the history and culture of Elazığ. Additionally, a video of a Sela performance, accessed via online channels from the source person, was transcribed into musical notation using standard musical transcription methods with the person's permission. This transcribed work is presented in the findings section of the research. Furthermore, a musical analysis of this work was performed using the document review method. The findings of the research show that the Harput region selas have a rich musical structure.The research concluded that the selas of the Harput region share similar musical structures and characteristics with Harput music (non-religious music). This suggests that the selas of the Harput region operate within an interactive framework that incorporates both religious and non-religious music within the local context. © 2025, Tolga Karaca. All rights reserved.
HARPUT YÖRESİ SELA İCRA PRATİKLERİNİN ETNOMÜZİKOLOJİK BOYUTU VE MÜZİKAL İNCELEMESİ: BİR MEVLÜT GENÇ ÖRNEĞİ
Keywords: ethnomusicological analysis; Harput region selas; Mevlüt Genç; musical analysis; religious music